Effects of Standardized Natural Citrus Extract on Growth, Gut Health, Carcass Quality, and Welfare of Broiler Chickens - Sekhou Cisse; Arkadiusz Matuszewski; Damian Bień; Patrycja Ciborowska; Anna Zalewska; Jakub Urban; Monika Michalczuk; Marta Mendel; Urszula Latek; Joanna Polak; Małgorzata Sobczak-Filipiak; Paweł Konieczka; et al. (Animals)
This study aimed to investigate the effects of a Standardized Natural Citrus Extract (SNCE) on broiler chickens’ growth performance, gut health, carcass quality, and welfare. A total of 756 one-day-old Ross 308 males were randomly assigned to two groups: a control group (CTL) fed with a standard diet, and a citrus group (SNCE) fed with the same standard diet supplemented with 250 g/ton of feed of SNCE. Growth performance was recorded weekly until d 35, while mortality was recorded daily. The feed conversion ratio (FCR) and European Efficiency Index (EEI) of broiler chickens were also calculated weekly. At day 35, 10 birds per group were randomly selected for slaughter performance. In parallel, broiler chickens’ welfare was assessed according to the Welfare Quality Assessment Protocol. Caecal digest was also collected post mortem for short-chain fatty acids (SCFA) analyses, and jejunum samples were collected for ex vivo gut permeability assay. SNCE dietary supplementation enhanced broiler chickens’ performance, i.e., final bodyweight and EEI, compared to the CTL group. The carcass weight was also significantly higher in the SNCE group. In addition, the fat percentage was lower in the SNCE group. Regarding broiler chickens’ welfare and gut health parameters, Footpad Dermatitis (FPD) and gate score were also lower in birds supplemented with SNCE. The SCFA measurement showed a lower concentration of iso-butyric acid, iso-valeric acid, and total putrefactive SCFA in the SNCE group. The differences in gut permeability measured as TEER value indicate that using citrus extract lowered the risk of gut inflammation. This study provides valuable insights into the mechanisms of action that may underlie the observed effects of SNCE on performance, as demonstrated in this study and others. These effects could potentially be attributed to the reduction in inflammation and the enhanced utilization of nutrients. Further studies are needed to confirm these results.